Fair Secure Dominating Set in the Corona of Graphs - Lorelyn P. Gomez; Enrico L. Enriquez (International Journal of Engineering and Management Research, 2020)
In this paper, we extend the concept of fair secure dominating sets by characterizing the corona of two nontrivial connected graphs and give some important results.